3D hardtissue database - Abdul Majid, Zakiah; Setan, Halim; Majid, Zulkepli; Chong, Albert K.; Ahmad, Anuar (2005)
This research focuses on the development of a 3D hardtissue database for craniofacial. This database is being developed to assist the medical profession to provide better health services to the public. 3 software are used in this research, i.e. 3D SLICER, RAPIDFORM2004 and MYSQL 4.1. 3D SLICER software is used for image-processing of Computed Tomography (CT) scanned data to get 3D computer model of human skulls. Then RAPIDFORM2004 software is used to identify and measure the landmarks on the 3D skulls. After 3D skulls were processed and landmarks were identified, the 3D hardtissue database is designed and developed to store the data. The database is developed using MYSQL 4.1 software for later retrieval.